Enhanced Production of Ethanol from Cheese whey by Agarose and Alginate immobilization of Yeast Cells - Shrestha, Smita; Shrestha, Fedip; Rajbhandari, Prajwal; Baral, Ramesh; Suwal, Shyam Krishna; Joshi, Jarina (Journal of Nepal Chemical Society, 2013)
Yeasts cells isolated from dry yeast were immobilized in alginate and agarose to form beads. The fermentation of ethanol from cheese whey was optimized with respect to temperature, pH, and rpm. A comparative study was performed between immobilized and free cells to get the maximum ethanol production Results revealed that 35°C temperature, 4.5 pH and 60 rpm is the optimized condition for yeast immobilized in agarose bead. Similarly, 35°C temperature, 5.0 pH, 60 rpm is the optimized condition for yeast immobilized in alginate bead and 35°C temperature, 5.0 pH, 80 rpm is the optimized condition for the free yeast cell respectively. Immobilised cell resulted 4.25% ethanol with alginate bead whereas 4.35% with agarose bead and 4.30% with free cell after three days of incubation under optimized conditions. When the same cell immobilized beads were reused, obtained 1.8% ethanol with agarose and 1.7% ethanol with alginate bead.DOI: http://dx.doi.org/10.3126/jncs.v30i0.9388Journal of Nepal Chemical Society Vol. 30, 2012 Page:  159-164 Uploaded date: 12/20/2013